2011
DOI: 10.2106/jbjs.j.01757
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Ultrasound Assessment of the Effects of Knee and Ankle Position on Achilles Tendon Apposition Following Acute Rupture

Abstract: Maximum ankle equinus alone significantly reduces the gap distance after acute Achilles tendon rupture. Increasing knee flexion further reduces the gap distance by small increments that, although significant, may not be clinically important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…5 Ultrasound may be used to identify the location of the rupture, the amount of tissue torn and, importantly, the ability of the torn tendon tissue to oppose in varying positions of equinus. 6,7 This is therefore an essential investigation. For patients who are treated conservatively, knowledge of the optimum position for immobilisation is obtained by using ultrasound to place the ankle in a position in which the ends of the tendon ends oppose, rather than overlap or fail to approximate.…”
mentioning
confidence: 99%
“…5 Ultrasound may be used to identify the location of the rupture, the amount of tissue torn and, importantly, the ability of the torn tendon tissue to oppose in varying positions of equinus. 6,7 This is therefore an essential investigation. For patients who are treated conservatively, knowledge of the optimum position for immobilisation is obtained by using ultrasound to place the ankle in a position in which the ends of the tendon ends oppose, rather than overlap or fail to approximate.…”
mentioning
confidence: 99%
“…Despite the fact that distal tendinous length has smaller change, it is still difficult to accurately locate the broken position because the tendon sheath remained relatively intact and distal tendon can slide up and down in the lumen of the sheath as well as due to local swelling [38]. Ultrasound can position broken end in surface of projection location, but errors may also occur with ankle joint plantarflexion or dorsiflexion [39]. Some doctors used ultrasound for positioning during surgeries, but they need to have ultrasound knowledge which makes it hard to promote this practice [40].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, several authors have recommended using an above the knee cast with a knee flexion to relax the gastrocnemius, which further reduces the gap distance. However, recent studies have indicated that tendon gap distance decreases by only 1 mm with a knee flexion in the order of 30°. Furthermore, this method has no clinical significance on the magnitude of change in gap distance and increases the risk of a thromboembolism because it is cumbersome.…”
Section: Discussionmentioning
confidence: 99%